Sustainable Restaurant Development Strategies for SMEs in Ubud, Gianyar, Bali - I Nyoman Arcana (Institut Pariwisata dan Bisnis Internasional, 2026)
This study aims to formulate development strategies for sustainable restaurants managed by local Balinese communities in the Ubud tourism area, where competition from foreign-owned restaurants has been increasing rapidly. While small and medium-sized enterprises (SMEs) owned by local residents remain competitive in the accommodation sector, locally owned restaurants often face stronger competition from establishments managed by foreign investors with greater access to capital, networks, and marketing capabilities. This research was conducted between June and August 2025 using a qualitative case study approach involving field observations and in-depth interviews with locally owned restaurant operators. A SWOT-based strategic analysis was applied to identify internal strengths and weaknesses as well as external opportunities and threats related to sustainable restaurant development. The analytical framework incorporates sustainability perspectives derived from the Triple Bottom Line approach and community-based tourism principles. The findings indicate that the main opportunities for locally owned restaurants lie in the increasing global demand for sustainable tourism and authentic local culinary experiences. However, local SMEs face several structural constraints, including limited financial capital, managerial capacity, access to sustainable technologies, and marketing networks. Strategic analysis highlights the importance of strengthening institutional support and collaboration among stakeholders. This study recommends the development of partnership models involving government institutions, local communities, and private sector actors to overcome capital and capacity barriers. Key strategies include training programs on sustainable restaurant management, improved access to micro-financing, and collaborative marketing initiatives to enhance the competitiveness and long-term sustainability of locally owned restaurants in tourism destinations.